Construction and Function of Thiolate-Bridged Diiron NxHy Nitrogenase Model Complexes - Yang, Dawei; Wang, Baomin; Qu, Jingping (Accounts of chemical research, 2024)
ConspectusBiological nitrogen fixation mediated by nitrogenases has garnered significant research interest due to its critical importance to the development of efficient catalysts for mild ammonia synthesis. Although the active center of the most studied FeMo-nitrogenases has been determined to be a complicated [Fe7S9MoC] hetero-multinuclear metal-sulfur cluster known as the FeMo-cofactor, the exact binding site and reduction pathway of N2 remain a subject of debate. Over the past decades, the majority of studies have focused on mononuclear molybdenum or iron centers as potential reaction sites. In stark contrast, cooperative activation of N2 through bi- or multimetallic centers has been largely overlooked and underexplored, despite the renewed interest sparked by recent biochemical and computational studies. Consequently, constructing bioinspired bi- or multinuclear metallic model complexes presents an intriguing yet challenging prospect. In this Account, we detail our long-standing research on the design and synthesis of novel thiolate-bridged diiron complexes as nitrogenase models and their application to chemical simulations of potential biological N2 reduction pathways.Inspired by the structural and electronic features of the potential diiron active center in the belt region of the FeMo-cofactor, we have designed and synthesized a series of new thiolate-bridged diiron nitrogenase model complexes, wherein iron centers with +2 or +3 oxidation states are coordinated by Cp* as carbon-based donors and thiolate ligands as sulfur donors. Through the synergistic interaction between the two iron centers, unstable diazene (NH═NH) species can be trapped to generate the first example of a [Fe2S2]-type complex bearing a cis-μ-η1:η1-NH═NH subunit. Significantly, this species can not only catalyze the reductive N-N bond cleavage of hydrazine to ammonia but also trigger a stepwise reduction sequence NH═NH → [NH2-NH]- → [NH]2-(+NH3) → [NH2]- → NH3. Furthermore, an unprecedented thiolate-bridged diiron μ-nitride featuring a bent Fe-N-Fe moiety was successfully isolated and structurally characterized. Importantly, this diiron μ-nitride can undergo successive proton-coupled electron transfer processes to efficiently release ammonia in the presence of separate protons and electrons and can even be directly hydrogenated using H2 as a combination of protons and electrons for high-yield ammonia formation. Based on combined experimental and computational studies, we proposed two distinct reductive transformation sequences on the diiron centers, which involve a series of crucial NxHy intermediates. Moreover, we also achieved catalytic N2 reduction to silylamines with [Fe2S2]-type complexes by ligand modulation.Our bioinspired diiron cooperative scaffold may provide a suitable model for probing the potential N2 stepwise reduction pathways from the molecular level. Different from the traditional alternating and distal pathways dominated by mononuclear iron or molybdenum complexes, our proposed alternating transformation route based on the diiron centers may not involve the N2H4 intermediate, and the convergence point of the alternating and terminal pathways is imide, not amide. Our research strategy could inform the design and development of new types of bioinspired catalysts for mild and efficient nitrogen reduction in the future.ConspectusBiological nitrogen fixation mediated by nitrogenases has garnered significant research interest due to its critical importance to the development of efficient catalysts for mild ammonia synthesis. Although the active center of the most studied FeMo-nitrogenases has been determined to be a complicated [Fe7S9MoC] hetero-multinuclear metal-sulfur cluster known as the FeMo-cofactor, the exact binding site and reduction pathway of N2 remain a subject of debate. Over the past decades, the majority of studies have focused on mononuclear molybdenum or iron centers as potential reaction sites. In stark contrast, cooperative activation of N2 through bi- or multimetallic centers has been largely overlooked and underexplored, despite the renewed interest sparked by recent biochemical and computational studies. Consequently, constructing bioinspired bi- or multinuclear metallic model complexes presents an intriguing yet challenging prospect. In this Account, we detail our long-standing research on the design and synthesis of novel thiolate-bridged diiron complexes as nitrogenase models and their application to chemical simulations of potential biological N2 reduction pathways.Inspired by the structural and electronic features of the potential diiron active center in the belt region of the FeMo-cofactor, we have designed and synthesized a series of new thiolate-bridged diiron nitrogenase model complexes, wherein iron centers with +2 or +3 oxidation states are coordinated by Cp* as carbon-based donors and thiolate ligands as sulfur donors. Through the synergistic interaction between the two iron centers, unstable diazene (NH═NH) species can be trapped to generate the first example of a [Fe2S2]-type complex bearing a cis-μ-η1:η1-NH═NH subunit. Significantly, this species can not only catalyze the reductive N-N bond cleavage of hydrazine to ammonia but also trigger a stepwise reduction sequence NH═NH → [NH2-NH]- → [NH]2-(+NH3) → [NH2]- → NH3. Furthermore, an unprecedented thiolate-bridged diiron μ-nitride featuring a bent Fe-N-Fe moiety was successfully isolated and structurally characterized. Importantly, this diiron μ-nitride can undergo successive proton-coupled electron transfer processes to efficiently release ammonia in the presence of separate protons and electrons and can even be directly hydrogenated using H2 as a combination of protons and electrons for high-yield ammonia formation. Based on combined experimental and computational studies, we proposed two distinct reductive transformation sequences on the diiron centers, which involve a series of crucial NxHy intermediates. Moreover, we also achieved catalytic N2 reduction to silylamines with [Fe2S2]-type complexes by ligand modulation.Our bioinspired diiron cooperative scaffold may provide a suitable model for probing the potential N2 stepwise reduction pathways from the molecular level. Different from the traditional alternating and distal pathways dominated by mononuclear iron or molybdenum complexes, our proposed alternating transformation route based on the diiron centers may not involve the N2H4 intermediate, and the convergence point of the alternating and terminal pathways is imide, not amide. Our research strategy could inform the design and development of new types of bioinspired catalysts for mild and efficient nitrogen reduction in the future.